Development Of Political Communication In Uzbekistan: Problems And Prospects - pcadmin, pcadmin (Global Scientific Publishing, 2025)
This article explores the evolution of political communication in Uzbekistan, focusing on the challenges and opportunities that have arisen in the context of recent political reforms and societal changes. Political communication encompasses various forms of interaction between government institutions, political actors, and the public, playing a critical role in shaping public opinion and facilitating democratic governance. The analysis begins with a historical overview of political communication in Uzbekistan, tracing its roots from the Soviet era to the present day. It highlights significant shifts in communication strategies, particularly following the 2016 presidential transition, which marked the beginning of a new phase of openness and engagement with civil society
Keywords: Political Communication; Uzbekistan; Media Reform